Design Principles for FES Concept Development - Dakin, Samuel (Cranfield University, 2013)
A variety of pathologies can cause injury to the spinal cord and hinder movement. A range of equipment is available to help spinal injury sufferers move their affected limbs. One method of rehabilitation is functional electrical stimulation (FES). FES is a technique where small electrical currents are applied to the surface of the user’s legs to stimulate the muscles. Studies have demonstrated the benefits of using this method and it has also been incorporated into a number of devices. The aim of the project was to produce a number of designs for a new device that uses FES technology. The project was completed in conjunction with an industrial partner. A review of the literature and consultation with industrial experts suggested a number of ways current devices could be improved. These included encouraging the user to lean forwards while walking and powering the device using a more ergonomic method. A group of designers were used to produce designs that allowed the user to walk with a more natural gait and avoided cumbersome power packs. The most effective of these designs were combined to form one design that solved both problems. A 3-dimensional model of this design was simulated using computer-aided design software. Groups of engineers, scientists and consumers were also invited to provide input on how a new device should function. Each of these groups provided a design that reflected their specific needs, depending on their experience with similar technology. Low level prototypes were produced of these designs. A group of designers were also used to design concepts for a functional electrical stimulation device based on an introduction given by industry experts. Each of the designs was presented to experienced professionals to obtain feedback. A set of guidelines were also produced during the project that instructed how to create the designs.
© Cranfield University 2013. All rights reserved. No part of this publication may be reproduced without the written permission of the copyright owner.
Keywords: Spinal Injury; Rehabilitation; Walking; Exoskeleton; Muscular Stimulation